2020
DOI: 10.1038/s41598-020-63018-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-harvest climate and post-harvest acclimation to cold prevent from superficial scald development in Granny Smith apples

Abstract: Superficial scald is one of the most serious postharvest physiological disorders that can affect apples after a prolonged cold storage period. This study investigated the impact of pre-and post-harvest climatic variations on superficial scald in a susceptible apple cultivar. Fruit batches with contrasting phenotypes for superficial scald incidence were identified among several years of "Granny Smith" fruit production. The "low scald" year pre-harvest climate was characterised by a warm period followed by a sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The ROS processing system and its related gene network during post-harvest cold acclimation promotes fruit resistance to oxidative stress and limits superficial scald development in apples [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROS processing system and its related gene network during post-harvest cold acclimation promotes fruit resistance to oxidative stress and limits superficial scald development in apples [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…APX activity was higher in scald-resistant pears than that in scald-susceptible ones, with different sunlight-exposure [11], and in 'Wujiuxiang' pears treated with 1-MCP with low scald incidence [18]. The ROS processing system and its related gene network during post-harvest cold acclimation promotes fruit resistance to oxidative stress and limits superficial scald development in apples [51].…”
Section: Antioxidantenzymes In Flesh and Peel Of Different Cultivar/smentioning
confidence: 99%
“…Studies have shown that cytosine methylation-based epigenetic regulation is involved in scald resistance (Karagiannis et al 2018), and a crucial role of polyphenol oxidase (PPO) and especially of the glutathione S-transferase (GST) protein in scald progress has been suggested (Karagiannis et al 2020). Previous reports showed that pre-harvest climate and post-harvest acclimation to cold and intermittent warming prevent superficial-scald development in Granny Smith apples (Honass et al 2019;Marc et al 2020). Lastly, recent research indicated that superficial scald was closely related to PCD (Busatto et al 2014;Du et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2019; Marc et al . 2020). Lastly, recent research indicated that superficial scald was closely related to PCD (Busatto et al .…”
Section: Introductionmentioning
confidence: 99%
“…After long-term cold storage, pears appear to develop superficial scald, which is similar to that in apples. Previous investigation have suggested that this phenomenon is related to the metabolism of α-farnesene and especially the accumulation of conjugated trienols (Whitaker et al, 2000, Whitaker, 2007, 2013Lurie and Watkins, 2012;Zhou et al, 2017), and reactive oxygen species (ROS; Marc et al, 2020) as well as phenolic acids and flavonoids (Piretti et al, 1996;Zhi and Dong, 2018;Cebulj et al, 2020). 3-Hydroxy-3-methylglutaryl-CoA reductase (HMGR) and α-farnesene synthase (AFS) are key synthesis enzymes (Lurie and Watkins, 2012), and the HMGR and AFS genes expression is associated with α-farnesene and scald development (Gapper et al, 2006;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%